Mutational Pattern Induced by 5-Fluorouracil and Oxaliplatin in the Gut Microbiome - Wan, Li; Li, Hexin; Sun, Gaoyuan; Zhang, Lili; Xu, Hongtao; Su, Fei; He, Shunmin; Xiao, Fei (Frontiers in Microbiology, 2022)
Chemotherapeutic agents, such as 5-Fluorouracil (5-FU) and Oxaliplatin (Oxi), can not only kill the cancer cell but also influence the proliferation of gut microbiota; however, the interaction between these drugs and gut microbiota remains poorly understood. In this study, we developed a powerful framework for taxonomy composition and genomic variation analysis to investigate the mutagenesis effect and proliferation influence of chemotherapeutic agents, such as 5-Fluorouracil (5-FU) and Oxaliplatin (Oxi) on gut microbiota, and the interaction between these drugs and gut microbiota during chemotherapy. Using the gut microbiome data, we detected 1.45 million variations among the chemotherapy groups and found the drugs significantly affected mutation signatures of gut microbiota. Oxi notably increase transversion rate, while 5-FU reduced the rate. Traits related to cell division and nutrient mobilization showed evidences of strong selection pressure from chemotherapeutic agents. In addition, drug-associated bacteriome shift patterns and functional alterations were found: the metabolism changes in the 5-FU group implied that gut microbiota could provide additional NAD+ to inhibit cancer cell autophagy; in the Oxi group, the ribosome and lysine biosynthesis genes were obviously enriched. Our study provides a blueprint for characterizing the role of microbes and drug-microbe interaction in the gut microbiota response to chemotherapy.